Comparative Analysis of Endodontic 0.15 Stainless-Steel K-Files: Exploring Design, Composition, and Mechanical Performance - Abayomi Omokeji Baruwa; Filipa Chasqueira; Sofia Arantes-Oliveira; João Caramês; Duarte Marques; Jaime Portugal; Jorge N. R. Martins (MDPI AG, 2024)
To establish a glide path, smaller files (up to size 0.15) with tapers of 2% are commonly used as pathfinding files. They pre-shape the root canal space before transitioning to larger taper endodontic instruments, aiming to prevent procedural errors. This study aimed to compare the design, metal wire composition, and mechanical characteristics of seven different ISO size 15 stainless-steel hand files (K-File and C-File+). Ninety-one new stainless-steel ISO 15 K-files were mechanically tested. All files were inspected for deformations before the assessment. Dental operating microscope, scanning electron microscope (SEM), and optical microscope analyses were conducted on four randomly selected instruments from each group, and two instruments per group underwent an energy-dispersive X-ray spectroscopy (EDS) analysis. Buckling mechanical tests were performed using an Instron universal testing machine, and microhardness was assessed using a Vickers hardness tester. The statistical analysis employed the nonparametric Mood's median test, with a significance level set at 0.05. The instrument design analysis unveiled variations in the active blade area length and the number of spirals, while maintaining consistent cross-sections and symmetrical blades. Distinct tip geometries and surface irregularities were observed. While the energy-dispersive X-ray spectroscopy confirmed similar compositions, the buckling strength and microhardness values exhibited variability across for all tested files. Notably, the Dentsply ReadySteel C-File+ recorded the highest buckling value (2.10 N), and the Dentsply ReadySteel K-File exhibited the lowest (1.00 N) (p < 0.05). Moreover, the Dentsply ReadySteel K-File recorded the highest microhardness value (703 HVN), while the SybronEndo Triple-Flex had the lowest (549 HVN) (p < 0.05). While similarities in cross-section design and metal wire composition were noted among the files, variations in the number of spirals and mechanical performance were also observed. Thus, all of these factors should be considered when selecting suitable files for an efficient root canal treatment.